The effectiveness of borrower-based macroprudential policies: A cross-country analysis using an integrated micro-macro simulation model - Stelios Giannoulakis; Marco Forletta; Marco Groß; Eugen Tereanu (European Central Bank (ECB), 2023)
This paper evaluates the resilience benefits of borrower-based macroprudential policies-such as LTV, DSTI, or DTI caps-for households and banks in the EU. To that end, we employ a further developed variant of the integrated micro-macro simulation model of Gross and Población (2017). Besides various methodological advances, joint policy caps are now also considered, and the resilience benefits are decomposed across income and wealth categories of borrowing households. Our findings suggest that (1) the resilience of households improves notably as a result of implementing individual and joint policy limits, with joint limits being more than additively effective; (2) borrower-based measures can visibly enhance the quality of bank mortgage portfolios over time, supporting bank solvency ratios; and (3) the policies' resilience benefits are more pronounced for households located at the lower end of the income and wealth distributions.
Keywords: C33; E58; G18; 330; Borrower-based macroprudential policy; household micro data and modeling; macro-financial linkages